Transfer of computer-based assessment to in-situ performance in novice field hockey goalkeepers - Lim, J. Z.; Kong, P. W. (Sports Engineering, 2025)
Field hockey goalkeeping requires a combination of decision-making and physical skills to perform well under pressure. While computer-based tasks have been used as a decision-making testing tool, such relevance to actual goalkeeping performance remains unclear in novice goalkeepers. This study examined whether performance in computer-based decision-making tasks could be transferred to in-situ field hockey goalkeeping, and whether reaction tests and physical attributes could predict successful goalkeeping performance. A total of 17 participants completed a series of computer-based and actual goalkeeping tasks, as well as seated and physical reaction tests. Results suggested that while response accuracy did not significantly differ between computer-based and in-situ tasks (p = 0.901), some individuals performed better in the computer-based task while others performed better in the actual goalkeeping task. Seated reaction task accuracy was a significant predictor of computer-based response accuracy (p = 0.012). However, in-situ performance could not be predicted from computer-based results, reaction tests or physical attributes. The study indicated no transferability of decision-making performance from computer-based to in-situ field hockey goalkeeping tasks in novice goalkeepers. Physical and anthropometrical variables also did not contribute to predicting successful goalkeeping performances. These findings caution against solely using computer tests to assess an individual`s potential to perform as a field hockey goalkeeper.